Reverse Shoulder Arthroplasty Baseplate Stability Is Affected by Bone Density and the Type and Amount of Augmentation - Daniel Ritter; Patric Raiss; Patrick J. Denard; Brian C. Werner; Manuel Kistler; Celina Lesnicar; Micheal van der Merwe; Peter E. Müller; Matthias Woiczinski; Coen A. Wijdicks; Samuel Bachmaier (Bioengineering)
Objective: This study evaluated the effects of bony increased offset (BIO) and metallic augments (MAs) on primary reverse shoulder arthroplasty (RSA) baseplate stability in cadaveric specimens with variable bone densities. Methods: Thirty cadaveric specimens were analyzed in an imaging and biomechanical investigation. Computed tomography (CT) scans allowed for preoperative RSA planning and bone density analysis. Three correction methods of the glenoid were used: (1) corrective reaming with a standard baseplate, which served as the reference group (n = 10); (2) MA-RSA (n = 10); and (3) angled BIO-RSA (n = 10). Each augment group consisted of 10° (n = 5) and 20° (n = 5) corrections. Biomechanical testing included cyclic loading in an articulating setup, with optical pre- and post-cyclic micromotion measurements in a rocking horse setup. Results: There were no differences in bone density between groups based on CT scans (p > 0.126). The BIO-RSA group had higher variability in micromotion compared to the MA-RSA and reference groups (p = 0.013), and increased total micromotion compared to the reference group (p = 0.039). Both augmentations using 20° corrections had increased variance in rotational stability compared to the reference group (p = 0.043). Micromotion correlated with the subchondral bone density in the BIO-RSA group (r = −0.63, p = 0.036), but not in the MA-RSA (p > 0.178) or reference (p > 0.117) groups. Conclusions: Time-zero baseplate implant fixation is more variable with BIO-RSA and correlates with bone density. Corrections of 20° with either augmentation approach increase variability in rotational micromotion. The preoperative quantification of bone density may be useful before utilizing 20° of correction, especially when adding a bone graft in BIO-RSAs.